Comparison of hemagglutination inhibition test and enzyme-linked immunosorbent assay for determining antibody to rubella virus. - Shekarchi, I C (1981)
The hemagglutination inhibition test (HAI) and the enzyme-linked immunosorbent assay (ELISA) for detecting antibody to rubella virus were compared by testing 25 sets of paired sera taken before and after infection and 10 sets of sera taken during acute and convalescent stages of the disease and by screening 700 serum samples from the Collaborative Perinatal Project, NIH/NINCDS. The tests were found to be comparable in their ability to detect positive and negative sera, rises in titers, and seroconversions. When a purified antigen and carefully prepared reagents were used, ELISA was found to be as accurate and reliable as HAI. ELISA required no pretreatment of serum, could easily be automated, and was less time-consuming than HAI.